2015
DOI: 10.1159/000433446
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Prelemniscal Radiations as a Target for Motor Symptoms in Parkinson's Disease Treatment

Abstract: Objective: To better define prelemniscal radiations (Raprl) as a target for the control of tremor and rigidity in Parkinson's disease (PD). Methods: A total of 36 deep brain stimulation (DBS) electrodes were stereotactically implanted in Raprl contralateral to the extremities to be treated. Effects on symptoms were evaluated using UPDRS-III before and after DBS, and significance was determined using the Wilcoxon test. The location of DBS contacts in cases with optimum versus suboptimum results was evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…We must keep in mind that the stimulated area is composed of fibers and not of nuclei, as determined by structural MRI ( fig. 1 ) and transoperative microelectrode recordings [22] . Assuming that regional metabolic activity is indirect evidence of neuronal activity, Raprl-DBS would inhibit local fibers and areas ana- With each ROI the number of readings included in statistical analysis (n) is provided for each side.…”
Section: Discussionmentioning
confidence: 99%
“…We must keep in mind that the stimulated area is composed of fibers and not of nuclei, as determined by structural MRI ( fig. 1 ) and transoperative microelectrode recordings [22] . Assuming that regional metabolic activity is indirect evidence of neuronal activity, Raprl-DBS would inhibit local fibers and areas ana- With each ROI the number of readings included in statistical analysis (n) is provided for each side.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations began in the 1960s with selective ablation (Bertrand, Hardy, Molina‐Negro, & Martínez, 1969; Mundinger, 1965; Spiegel et al, 1962, 1964; Spiegel & Wycis, 1954; Velasco, Velasco, & Machado, 1975; Wertheimer, Lapras, & Levy, 1960), but as technologies improved, various groups (Blomstedt, Sandvik, & Tisch, 2010; Mohadjer, Goerke, Milios, Etou, & Mundinger, 1990; Nowacki et al, 2018; Plaha, Ben‐Shlomo, Patel, & Gill, 2006; Velasco et al, 2001) demonstrated that electrical stimulation to these regions was also effective. Yet because of poor direct visualization, controversy has remained as to whether the therapeutic effect is derived from modulation of the cell bodies in the cZI, wayward connections such as the fasciculus cerebellothalamicus (fct; also known as the prelemniscal radiations or raprl) (Castro et al, 2015; Velasco, Molina‐Negro, Bertrand, & Hardy, 1972), or some combination of both (Blomstedt et al, 2010). Given the ambiguity and high functional density of the region, the stereotactic target is often considered more broadly as the posterior subthalamic area (PSA; Blomstedt et al, 2018; Hariz & Blomstedt, 2017; Nowacki, Debove, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Raprl-DBS has been found to be effective in controlling tremor, rigidity, bradykinesia, and gait disturbances in PD patients [12, 13]; however, in patients with a predominant unilateral tremor the concomitant hypotonia induced by Raprl-DBS or lesioning induces the sensation of instability and claudication in the contralateral leg during gait, jeopardizing the results of surgical treatment. In one such case a discrete lesion of the cerebellar-Vim component, sparing the anterior cerebellar-Vop fibers, resulted in selective control of the tremor without hypotonia or claudication of the contralateral leg.…”
Section: Introductionmentioning
confidence: 99%